Pandangan Non Muslim mengenai Eksistensi Jurnalis Televisi Berjilbab - Cahyaningrum, Indah Ayu; Khoyin, Muhamad; Dulwahab, Encep (Annaba: Jurnal Ilmu Jurnalistik, 2020)
The study aims to determine the nonmuslims’s view especially the Congregation of Gereja Pantekosta di Indonesia (GPdI) Imanuel Babelan regarding the role of hijabi women as journalists in television media, professionalism and ability of hijabi journalists, and to determine their interest in watching news brought by hijabi journalists. The method used in this research is a qualitative descriptive study with constructivism paradigm. The results of the study show that: (1) the GPdI Imanuel Babelan congregation views hijabi journalists as journalists who are polite, elegant, and pure in sight, (2) they thinks that hijabi journalists report more Islamic moments than other religion moments, (3) the existence of hijabi journalists on television does not reduce the congregation's interest in watching news shows.